2013
DOI: 10.1121/1.4801077
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between gesture, tone production and perception in classical cello performance

Abstract: On bowed string instruments such as violin or cello, the quality of sound depends mostly on the performer's bowing technique, which determines the interaction between the bow hair and the string. An accomplished string player has numerous ways of shaping the spectrum of a desired sound. This research investigates the combination of bowing gestures necessary for production of a rich tone. In particular, bowing control parameters such as bow force, bow velocity and bow-bridge distance captured by a dedicated sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…In terms of brightness (spectral roll-off), the largest difference was observed between perf2 and perf5 and the smallest between perf4 and perf5. Similar results for the three cellists were obtained in [15] for spectral centroid identified as the parameter most strongly correlated with the brightness dimension when a larger set of audio samples from various music excerpts was analyzed and compared. While different methods of feature calculations and advanced statistical analyses were employed in the former work, this example shows the usefulness of the tool in gaining preliminary insights into the studied data and helping to formulate initial research hypotheses.…”
Section: Case Studies a Exploring Timbre Dissimilarities Of Cello Pla...supporting
confidence: 70%
See 3 more Smart Citations
“…In terms of brightness (spectral roll-off), the largest difference was observed between perf2 and perf5 and the smallest between perf4 and perf5. Similar results for the three cellists were obtained in [15] for spectral centroid identified as the parameter most strongly correlated with the brightness dimension when a larger set of audio samples from various music excerpts was analyzed and compared. While different methods of feature calculations and advanced statistical analyses were employed in the former work, this example shows the usefulness of the tool in gaining preliminary insights into the studied data and helping to formulate initial research hypotheses.…”
Section: Case Studies a Exploring Timbre Dissimilarities Of Cello Pla...supporting
confidence: 70%
“…The aim of the study was to reveal whether classical musicians can be discriminated by their tone quality using extracted acoustic parameters. The major experiments and research results were reported in [15].…”
Section: Case Studies a Exploring Timbre Dissimilarities Of Cello Pla...mentioning
confidence: 99%
See 2 more Smart Citations